Anti-aging wear-resistant cable and preparation process thereof

Through the combined design of wear-resistant surface layer, phase change layer and support layer, combined with the autonomous circulation heat dissipation system and thixotropic phase variant, the heat dissipation and aging problems of the cable during high-power charging and frequent bending are solved, and the active heat dissipation and anti-aging effects of the cable are achieved.

CN120413167APending Publication Date: 2025-08-01ZHEJIANG LANSHENG COMM TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510615980.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

Existing cables are difficult to dissipate heat during high-power charging, the insulation layer ages quickly, and are easily damaged when frequently plugged and unplugged, which cannot effectively extend the service life.

Method used

We adopt wear-resistant surface layer, phase change layer and support layer structure, combined with elastic partition walls, controllable valve channels and inner frame design, to form an autonomous circulating heat dissipation system, and use thixotropic phase variants and piezoelectric ceramic fibers to reduce stress and enhance flexibility.

Benefits of technology

It realizes the active heat dissipation and anti-aging effects of the cable, extends the service life, improves flexibility and bending resistance, and reduces the heat accumulation and wear of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120413167A_ABST
    Figure CN120413167A_ABST
Patent Text Reader

Abstract

The invention relates to the related technical field of cables, and discloses an anti-aging wear-resistant cable and a preparation technology thereof.The cable core and a skin layer wrapping the cable core are characterized in that the skin layer comprises a wear-resistant surface layer, a phase change layer and a supporting layer from outside to inside, and the cable core is wrapped by the supporting layer; the phase change layer comprises closed cavities defined by elastic partition walls, the adjacent cavities are communicated through controllable valve channels, the cavities are filled with thixotropic phase change bodies, the thixotropic phase change bodies are in a gel state in a static state and are converted into a sol state when being pressed, an elastic supporting net is arranged in the supporting layer, the cable core is wrapped by the elastic supporting net, and the cable core is arranged in the supporting layer. The cable has the self-circulation heat dissipation function, liquid in the flexible pipeline actively flows into the grooves of the wear-resistant surface layer through the heat conduction channels and the small holes, the liquid is dispersed on the outer side, the heat dissipation efficiency is improved, the heat dissipation area is increased, and the heat dissipation efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to lighting equipment. More specifically, it particularly relates to an anti-aging and wear-resistant cable and its preparation process. Background Art

[0002] With the development of power transmission technology, the demand for high-power cables in fields such as new energy charging piles, data centers, and electric vehicle fast charging is increasing day by day. However, during the high-current charging process, a large amount of heat is generated inside the cable. If the heat cannot be dissipated in time, it will cause the cable temperature to rise sharply, accelerate the aging of the insulation layer, reduce the conduction efficiency, and even pose a safety hazard. Therefore, how to improve the active heat dissipation ability of the cable, enhance flexibility, and extend the service life has become an urgent problem to be solved in current cable technology.

[0003] With the popularization of new energy vehicle fast charging technology and high-frequency industrial automation equipment, the working environment of cables has become increasingly harsh, especially facing severe challenges in the following scenarios: Instantaneous high heat load: When using high-voltage fast charging, the current increases instantaneously, and the temperature of the cable core can rise to a relatively high temperature within a few minutes, posing a challenge to the high-temperature resistance of the cable material; Frequent plugging and unplugging and bending: The cable of the public charging gun is bent many times every day, and the traditional sheath material is prone to generate microcracks due to repeated stress, accelerating the aging of the internal insulation layer; Dynamic heat dissipation problem: When the cable moves, it is easy to cause heat to accumulate at the bending part, forming local hot spots.

[0004] Therefore, in view of this, research and improvement are carried out on the existing structure and deficiencies, and an anti-aging and wear-resistant cable and its preparation process are provided, with the expectation of achieving a more practical value. Summary of the Invention

[0005] The present invention provides an anti-aging and wear-resistant cable and its preparation process to overcome the above-mentioned defects in the prior art.

[0006] The purpose and effect of an anti-aging and wear-resistant cable and its preparation process of the present invention are achieved by the following specific technical means: An anti-aging and wear-resistant cable includes a cable core and a cortex wrapped outside the cable core. The cortex includes a wear-resistant surface layer, a phase change layer, and a support layer from outside to inside. The cable core is wrapped by the support layer; the phase change layer includes sealed cavities surrounded by elastic partitions, and adjacent cavities are connected through controllable valve channels. The cavities are filled with a thixotropic phase variant, which is in a gel state when static and turns into a sol state when pressed. An elastic support net is provided in the support layer, and the elastic support net wraps the cable core.

[0007] It should be noted that the wear-resistant surface layer resists mechanical wear, the phase change layer actively absorbs heat, and the support layer disperses stress, forming a "hard outside and soft inside" collaborative protection. When the cable is bent, the local elastic partition wall is compressed and deformed, and the thixotropic phase variant changes from the gel state to the sol state, with a decrease in viscosity and an increase in fluidity. It flows through the controllable valve channel to automatically adjust the local volume, reduce the stress generated by cable bending, extend the service life of the cable, and achieve the effect of anti-aging. The elastic support net wraps the cable core, reducing the bending radius of the cable and supporting the phase change layer.

[0008] A further technical solution is that the wear-resistant surface layer is composed of the following components in parts by mass: 100 parts of polyurethane matrix, 20 - 30 parts of silicon carbide micropowder (particle size 5 - 15 μm), 1 - 3 parts of graphene nanosheets (thickness ≤ 5 nm), and 0.5 - 1 part of antioxidant 1010.

[0009] A further technical solution is that the preparation process of the wear-resistant surface layer includes: S1. Mix the polyurethane matrix and silicon carbide micropowder in a kneader at a temperature of 120 - 140 °C for 15 minutes; S2. Add graphene nanosheets and antioxidant, and extrude and pelletize through a twin-screw extruder; S3. Use a three-layer coextrusion die to coat the outside of the phase change layer. The outer layer is a wear-resistant composite material, the middle layer is an EVA buffer layer with a thickness ratio of 20%, and the inner layer is carbon black-modified TPU.

[0010] It should be noted that the silicon carbide micropowder improves the wear resistance of the surface layer, the graphene nanosheets form a lateral heat conduction network to reduce the surface temperature, the antioxidant 1010 captures free radicals to extend the service life of the surface layer under UV irradiation, the EVA buffer layer absorbs impact energy, and the carbon black-modified TPU inner layer prevents static electricity accumulation.

[0011] A further technical solution is that the thixotropic phase variant is composed of the following components: 70 - 80 wt% white oil, 8 - 12 wt% organic bentonite, 10 - 15 wt% microencapsulated paraffin, and 1 - 2 wt% nano-silica.

[0012] A further technical solution is that the preparation process of the thixotropic phase variant is: heat the white oil to 60 °C and then add organic bentonite, and ultrasonically disperse for 30 minutes; cool down to 40 °C and then add microencapsulated paraffin and nano-silica, and process with a high-shear emulsifier at a rotation speed of 8000 rpm for 10 minutes.

[0013] It should be noted that the microencapsulated paraffin absorbs heat at 40 - 60 °C, the organic bentonite imparts thixotropy, the nano-silica forms a three-dimensional network to prevent the settlement of fillers, and high-shear emulsification makes the microcapsules evenly dispersed.

[0014] A further technical solution is that the elastic partition is a polyurethane-carbon nanotube composite material, in which piezoelectric ceramic fibers are dispersed, and the surface of the elastic partition has corrugated protrusions.

[0015] A further technical solution is that the controllable valve channel includes: a channel body and a valve structure. The channel body is a conical hole, and the valve structure is a thin film covering the small end of the conical hole. A cross-shaped micro-slit is formed by laser processing in the center of the thin film.

[0016] It should be noted that when the piezoelectric ceramic fibers generate electrical signals when the partition bends, due to the resistance effect, the electricity is converted into heat, and the heat is transferred to the thixotropic phase variant through the carbon nanotubes to accelerate the reduction of the viscosity of the thixotropic phase variant. When the viscosity of the phase variant decreases and the fluidity increases, the closed cavity surrounded by the partition squeezes the phase variant under the action of pressure. After the pressure exceeds the elastic restoring force of the cross micro-slit, the fluid will flow to the adjacent cavity to reduce the pressure of the original cavity and reduce the resistance of the cable bending.

[0017] A further technical solution is that an inner skeleton is also provided inside the support layer. The inner skeleton includes a flexible pipe in the center and a support body circumferentially arranged outside the flexible pipe. Adjacent support bodies form a fan-shaped area. The cable core includes multiple strands, and each strand is distributed in one of the fan-shaped areas. The support body has a heat conduction channel communicating with the flexible pipe inside, and the flexible pipe is used to guide the fluid to dissipate heat.

[0018] A further technical solution is that small holes are opened on the wear-resistant surface layer, small-diameter pipelines are arranged in the small holes, the small-diameter pipelines penetrate inward through the phase change layer and communicate with the heat conduction channels. The surface of the wear-resistant layer is concave to form an axially extending groove. The small holes are distributed on the bottom wall of the groove. A sealing strip is arranged at the opening of the groove. One end of the flexible pipe is provided with an elastic membrane to form a blind end. One end of the cable is sleeved with a liquid storage bag. The liquid storage bag communicates with the groove, and the flexible pipe communicates with the liquid storage bag through a return pipe. A radially extending shape memory alloy spring is arranged in the liquid storage bag. The expansion and contraction of the shape memory alloy spring can drive the liquid storage bag to expand or contract, so that the internal cold liquid is supplemented into the flexible pipe through the return pipe.

[0019] It should be noted that the function of the support body is to keep the cross-section of the inner cavity full and improve the compressive capacity. In addition, the support body itself also has heat dissipation ability, and together with the central flexible pipe and the liquid storage bag, it forms an efficient heat dissipation cycle.

[0020] A preparation process for an anti-aging and wear-resistant cable includes the following steps: S1. Preparation of the phase change layer: a) Using ultraviolet-cured polyurethane composite material, an axially extending hexagonal prism honeycomb structure is formed by DLP printing, and a 0.5 mm connecting part is reserved between adjacent honeycomb units; b) At the center of the connection part, a conical through-hole is machined using picosecond laser, with a cone angle of 60° ± 5°; c) After the PVDF film is pre-coated with glue, it is covered on the small end of the cone hole through vacuum hot pressing bonding; d) A cross-shaped micro-slit with a slit width of 20 - 30 μm is machined in the center of the film using excimer laser; e) The thixotropic phase change body is heated to the flowing state, vacuum infused through the liquid injection port, and then cooled and solidified; S2. Inner skeleton preparation: a) Extrude and mold a flexible pipe; b) Set up an auxiliary structure for preparing a heat conduction channel in the support body mold. Pour liquid silicone into the support body. Inject the liquid silicone into the mold, and embed a heat conduction graphite sheet before curing to form a heat conduction network. After the silicone solidifies, a composite structure that conducts heat and allows fluid to pass through the heat conduction channel is formed inside the support body; c) Insert the flexible pipe into the central hole of the support body to ensure that the flexible pipe is connected to the auxiliary flow channel; S3. Integral molding: a) Put the inner skeleton into the elastic support net, and after plasma treatment of the joint surface, cover it with a support layer; b) After the phase change layer is surface-activated, it is thermocompression-bonded with the support layer, and the pressure is controlled at 3 - 5 MPa to keep the phase change body in the gel state; c) Use a three-layer co-extrusion process to cover the wear-resistant surface layer, and synchronously embed small-diameter pipelines at the groove positions; d) Install the liquid storage bladder system and test the temperature control response threshold of the shape memory alloy spring.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The cable of this application has an independent circulating heat dissipation function. During the charging process of the cable, a large amount of heat is generated, and the heat accumulates in the center. In order to quickly dissipate this part of the heat, a fluid for heat absorption is accommodated in the flexible pipe. When the shape memory alloy spring is heated, the temperature breaks through the Af point, and its own contraction will drive the volume of the liquid storage bladder to contract. The cold liquid stored in the liquid storage bladder flows into the flexible pipe through the return pipe. The pressure in the flexible pipe increases, which will push the elastic membrane at the blind end to bulge. Under the pressure of the elastic membrane, the liquid inside the flexible pipe actively flows through the heat conduction channel and the small holes into the grooves of the wear-resistant surface layer. The liquid is dispersed on the outside, accelerating the heat dissipation efficiency. The cooled liquid flows back into the liquid storage bladder, and the shape memory alloy spring is affected by the cold liquid and cools down and returns to the initial extended length, completing an active heat dissipation cycle. The high-temperature liquid can flow radially from the center and quickly dissipate to the surface of the cable, increasing the heat dissipation area and accelerating the heat dissipation efficiency.

[0022] In addition, during the heat dissipation process, the hot liquid will pass through the small-diameter pipeline. Since the small-diameter pipeline passes through the thixotropic phase variant of the phase change layer, part of the heat is absorbed by the thixotropic phase variant, and the heat is quickly dispersed and absorbed, further reducing the heat dissipation effect. After the thixotropic phase variant absorbs part of the heat, its fluidity increases, improving the basic flexibility of the cable, making the anti-bending ability stronger, and being beneficial to extending the service life.

[0023] Finally, when the cable is locally bent, the local elastic partition wall is compressed and deformed. The piezoelectric ceramic fiber generates an electrical signal when the partition wall bends. Due to the resistance effect, the electricity is converted into heat, and the heat is transferred to the thixotropic phase variant through the carbon nanotubes to accelerate the reduction of the viscosity of the thixotropic phase variant. When the viscosity of the phase variant decreases and the fluidity increases, the enclosed cavity surrounded by the partition wall squeezes the phase variant under the action of pressure. After the pressure exceeds the elastic restoring force of the cross micro-slots, the fluid will flow into the adjacent cavity to reduce the pressure in the original cavity and reduce the resistance to cable bending. The thixotropic phase variant changes from the gel state to the sol state, the viscosity decreases, and the fluidity increases. It flows through the controllable valve channel to automatically adjust the local volume, reduce the stress generated by cable bending, extend the service life of the cable, and achieve the effect of anti-aging. Description of the Drawings

[0024] Figure 1 is a cross-sectional schematic diagram of one embodiment of the present invention; Figure 2 is a schematic structural diagram of one embodiment of the partition wall 14 in the present invention; Figure 3 is an enlarged structural schematic diagram of the groove 26 in the present invention; Figure 4 is a schematic structural diagram of the cross-section of the cable in the present invention; Figure 5 is a cross-sectional schematic diagram of another embodiment of the present invention; Figure 6 is a schematic cross-sectional view of another embodiment of the present invention; Figure 7 is a schematic diagram of the cooperation of the first fin 34 and the second fin 35 in another embodiment of the present invention; Figure 8 is a schematic diagram of the bent state of the first fin 34 and the second fin 35 in another embodiment of the present invention.

[0025] Description of the Reference Numerals: Wear-resistant surface layer 10, phase change layer 11, support layer 12, cable core 13, partition wall 14, cavity 15, channel body 17, thin film 18, flexible pipe 21, support body 22, small-aperture pipeline 25, groove 26, sealing strip 27, elastic film 28, liquid storage sac 29, shape memory alloy spring 31, sealing strip 32, through groove 33, first fin 34, second fin 35, annular sealed space 36. Detailed implementation mode

[0026] The following further describes in detail the implementation mode of the present invention in conjunction with the drawings and embodiments. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.

[0027] In the description of the present invention, unless otherwise specified, the meaning of "a plurality" is two or more; the terms "upper", "lower", "left", "right", "inner", "outer", "front end", "rear end", "head", "tail", etc. indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0028] In the description of the present invention, it should be noted that unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific situations. Embodiment

[0029] As Figure 1 - 4 shown, the present application provides an anti-aging and wear-resistant cable, including a cable core 13 and a cortical layer coated outside the cable core 13. The cortical layer includes a wear-resistant surface layer 10, a phase change layer 11, and a support layer 12 from outside to inside, and the cable core 13 is coated by the support layer 12; the phase change layer 11 includes a sealed cavity 15 surrounded by an elastic partition wall 14, and adjacent cavities 15 are connected through a controllable valve channel. The cavity 15 is filled with a thixotropic phase variant, which is in a gel state when static and changes to a sol state when pressed. An elastic support net is provided in the support layer 12, and the elastic support net wraps the cable core 13.

[0030] Preferably, the elastic partition wall 14 is a polyurethane-carbon nanotube composite material, and piezoelectric ceramic fibers are dispersed therein. The surface of the elastic partition wall 14 has corrugated protrusions.

[0031] Preferably, the controllable valve passage includes: a passage body 17 and a valve structure. The passage body 17 is a tapered hole, and the valve structure is a thin film 18 covering the small end of the tapered hole. A cross-shaped micro-slit is formed by laser processing in the center of the thin film 18.

[0032] Preferably, an inner skeleton is further provided inside the support layer 12. The inner skeleton includes a flexible pipe 21 in the center and a support body 22 circumferentially arranged outside the flexible pipe 21. Adjacent support bodies 22 form a fan-shaped area. The cable core 13 includes multiple strands, and each strand is distributed in one of the fan-shaped areas. The support body 22 has a heat conduction channel communicating with the flexible pipe 21 inside, and the flexible pipe 21 is used to guide fluid for heat dissipation.

[0033] Preferably, small holes are opened in the wear-resistant surface layer 10, and small-diameter pipelines 25 are arranged in the small holes. The small-diameter pipelines 25 penetrate inward through the phase-change layer 11 and communicate with the heat conduction channels. The surface of the wear-resistant layer is concave to form an axially extending groove 26. The small holes are distributed on the bottom wall of the groove 26. A sealing strip 27 is arranged at the opening of the groove 26. One end of the flexible pipe 21 is provided with an elastic membrane 28 to form a blind end. One end of the cable is sleeved with a liquid storage bladder 29. The liquid storage bladder 29 communicates with the groove 26, and the flexible pipe 21 communicates with the liquid storage bladder 29 through a return pipe. A radially extending shape memory alloy spring 31 is arranged in the liquid storage bladder 29. The expansion and contraction of the shape memory alloy spring 31 can drive the liquid storage bladder 29 to expand or contract, so that the internal cold liquid is supplemented into the flexible pipe 21 through the return pipe.

[0034] In this embodiment, the cable has an autonomous circulating heat dissipation function. The heat dissipation process is as follows: During the charging process of the cable, a large amount of heat is generated, and the heat accumulates in the center. In order to quickly dissipate this part of the heat, a fluid for heat absorption is accommodated in the flexible pipe 21. The liquid absorbs heat. After the shape memory alloy spring 31 is heated and the temperature breaks through the Af point, its own contraction will drive the volume of the liquid storage bladder 29 to contract. The cold liquid stored in the liquid storage bladder 29 flows into the flexible pipe 21 through the return pipe. The pressure in the flexible pipe 21 increases, which will push the elastic membrane 28 at the blind end to bulge. Under the pressure of the elastic membrane 28, the liquid inside the flexible pipe 21 actively flows into the groove 26 of the wear-resistant surface layer 10 through the heat conduction channel and the small holes. The liquid is dispersed on the outside to accelerate the heat dissipation efficiency. The cooled liquid flows back to the liquid storage bladder 29, and the shape memory alloy spring 31 is affected by the cold liquid and cools down to restore to its initial extended length, completing an active heat dissipation cycle.

[0035] During the heat dissipation process, the hot liquid will pass through the small-diameter pipeline 25. Since the small-diameter pipeline 25 passes through the thixotropic phase-changed body of the phase-change layer 11, part of the heat is absorbed by the thixotropic phase-changed body, and the heat is quickly dispersed and absorbed, further reducing the heat dissipation effect. And after the thixotropic phase-changed body absorbs part of the heat, its fluidity increases, improving the basic flexibility of the cable and making its anti-bending ability stronger, which is beneficial to extending the service life.

[0036] When a local bend occurs in the cable, the local elastic partition wall 14 is compressed and deformed. The piezoelectric ceramic fiber generates an electrical signal when the partition wall 14 bends. Due to the resistance effect, the electricity is converted into heat, and the heat is transferred to the thixotropic phase variant through the carbon nanotubes to accelerate the reduction of the viscosity of the thixotropic phase variant. When the viscosity of the phase variant decreases and the fluidity increases, the sealed cavity 15 surrounded by the partition wall 14 presses the phase variant under the action of pressure. After the pressure exceeds the elastic restoring force of the cross micro-slit, the fluid will flow into the adjacent cavity 15 to reduce the pressure of the original cavity 15 and reduce the resistance of the cable bending. The thixotropic phase variant changes from the gel state to the sol state, the viscosity decreases, and the fluidity increases. It flows through the controllable valve channel to automatically adjust the local volume, reduce the stress generated by the cable bending, extend the service life of the cable, and achieve the anti-aging effect.

[0037] In other embodiments of the present application, as Figure 5 - 8 shown, the form of the elastic partition wall 14 can also be a sheet, and the form of the sealed cavity 15 is a ring surrounding the outside of the support layer 12, and the fluid is more likely to flow in the ring-shaped sealed cavity 15.

[0038] Preferably, a through groove 33 with an axis is opened on the wall of the wear-resistant surface layer 10. A sealing strip 32 is arranged in the through groove 33. A number of first fins 34 are arranged in an array at the end of the sealing pipe strip extending into the through groove 33. And a number of second fins 35 are axially spaced and arranged in an array on the outer wall surface of the support layer 12. The first fins 34 and the second fins 35 are alternately distributed. The thixotropic phase variant is injected between the first fins 34 and the second fins 35. The materials of the first fins 34 and the second fins 35 are elastic, and the first fins 34 and the second fins 35 can also be supported by materials attached with piezoelectric ceramic fibers.

[0039] In this embodiment, when the cable bends, the first fins 34 and the second fins 35 also swing correspondingly. Due to their alternate distribution, the mutual swing will stir the thixotropic phase variant distributed in the ring-shaped sealed cavity 15. The thixotropic phase variant changes from the gel state to the sol state, the viscosity decreases, and the fluidity increases. It flows along the ring-shaped sealed space 36 to the side with an increased volume to reduce the resistance of the cable bending, improve the flexibility, and extend the service life.

[0040] Example 2, Preparation of the wear-resistant surface layer: Components: Polyurethane matrix: 100 parts, Silicon carbide micropowder: 25 parts, Graphene nanosheets: 2 parts, Antioxidant 1010: 0.8 parts Preparation process: Mix the polyurethane matrix and silicon carbide micropowder in a Banbury mixer at a temperature of 130°C for 15 minutes; add graphene nanosheets and antioxidant, and granulate through a twin-screw extruder at a temperature range of 170°C and a die head pressure of 12 MPa; use a three-layer co-extrusion die to coat the phase change layer, with the outer layer being a wear-resistant composite material with a thickness ratio of 60%, the middle layer being an EVA buffer layer with a thickness ratio of 20%, and the inner layer being carbon black-modified TPU with a thickness ratio of 20%.

[0041] Example 3, preparation of the wear-resistant surface layer: Components: Polyurethane matrix: 100 parts, silicon carbide micropowder: 20 parts, graphene nanosheets: 1 part, antioxidant 1010: 0.5 part.

[0042] Preparation process: Mix the polyurethane matrix and silicon carbide micropowder in a Banbury mixer at a temperature of 130°C for 15 minutes; add graphene nanosheets and antioxidant, and granulate through a twin-screw extruder at a temperature range of 180°C and a die head pressure of 12 MPa; use a three-layer co-extrusion die to coat the phase change layer, with the outer layer being a wear-resistant composite material with a thickness ratio of 60%, the middle layer being an EVA buffer layer with a thickness ratio of 20%, and the inner layer being carbon black-modified TPU with a thickness ratio of 20%.

[0043] Example 4, preparation of the wear-resistant surface layer: Components: Polyurethane matrix: 100 parts, silicon carbide micropowder: 30 parts, graphene nanosheets: 2 parts, antioxidant 1010: 0.8 part.

[0044] The preparation process is the same as that of Example 2.

[0045] Example 5, preparation of the thixotropic phase change body: Components: White oil: 75 wt%, organic bentonite: 10 wt%, microencapsulated paraffin wax: 12 wt%, nano-silica: 1.5 wt%.

[0046] Process: Heat the white oil to 60°C, add organic bentonite, and ultrasonically disperse for 30 minutes; cool down to 40°C, add microencapsulated paraffin wax and nano-silica, and process with a high-shear emulsifier at a rotation speed of 8000 rpm for 10 minutes.

[0047] Example 6, preparation of the thixotropic phase change body: Components: White oil: 70 wt%, organic bentonite: 12 wt%, microencapsulated paraffin wax: 15 wt%, nano-silica: 2 wt%.

[0048] The process is as follows: Heat white oil to 60°C, then add organic bentonite and disperse ultrasonically for 30 min. After cooling to 40°C, add microencapsulated paraffin and nano-silica, and process with a high-shear emulsifier at a rotation speed of 8000 rpm for 10 min.

[0049] Example 7, Preparation of thixotropic phase variant: Components: White oil: 70 wt%, Organic bentonite: 10 wt%, Microencapsulated paraffin: 15 wt%, Nano-silica: 1.5 wt%.

[0050] The process is the same as that of Example 5.

[0051] The following is the performance test comparison table of Examples 2 - 4: Example Silicon Carbide Micropowder (parts) Graphene Nanosheets (parts) Antioxidant 1010 (parts) Wear Loss (mg / 1000 revolutions) Surface Resistance (Ω) Tensile Strength (MPa) 2 25 2 0.8 18 <![CDATA[1.2×10 4 > 45 3 20 1 0.5 25 <![CDATA[3.5×10 4 > 38 4 30 2 0.8 12 9.8×10³ 50

[0052] Data analysis: When the silicon carbide content is increased to 30 parts (Example 4), the wear resistance is significantly improved, but the conductivity decreases slightly; the comprehensive performance of Example 3 is the weakest.

[0053] The following is the performance test comparison table of Examples 5 - 7: Example White Oil (wt%) Organic Bentonite (wt%) Microencapsulated Wax (wt%) Nano - Silicon Dioxide (wt%) Phase Change Enthalpy (J / g) Thixotropic Recovery Rate (25°C) Viscosity (Pa·s) 5 75 10 12 1.5 185 92% 48 6 70 12 15 2 205 88% 60 7 70 10 15 1.5 198 85% 55

[0054] Data analysis: When the white oil is reduced to 70 wt% and the microcapsule wax is increased to 15 wt%, the phase change enthalpy is increased by more than 10%, but the thixotropic recovery rate decreases slightly; the bentonite content has a significant effect on the viscosity.

[0055] Performance Index Optimal Example Key Influencing Factors Wear Resistance 4 Silicon Carbide 30 parts (upper limit) Phase Change Efficiency 6 White Oil 70wt% + Microencapsulated Wax 15wt% Thixotropic Stability 5 White Oil 75wt% + Bentonite 10wt%

[0056] Example 6, A preparation process for anti-aging and wear-resistant cables, includes the following steps: S1. Preparation of the phase change layer: a) Use a UV-cured polyurethane composite material to print an axially extending hexagonal prism honeycomb structure through DLP, leaving a 0.5 mm connecting part between adjacent honeycomb units; b) Use a picosecond laser to process a conical through-hole at the center of the connecting part, with a cone angle of 60° ± 5°; c) After pre-coating the PVDF film, cover the small end of the conical hole by vacuum hot pressing bonding; d) Use an excimer laser to process a cross-shaped micro-slit in the center of the film, with a slit width of 20 - 30 μm; e) Heat the thixotropic phase variant to the flowing state, and vacuum infuse it through the liquid injection port and then cool and solidify; S2. Preparation of the inner skeleton: a) Extrude a flexible pipe; b) providing an auxiliary structure for preparing a thermally conductive channel within the support mold, casting the support using liquid silicone. The liquid silicone is injected into the mold, and a thermally conductive graphite sheet is embedded in the mold before curing to form a thermally conductive network. After the silicone cures, a composite structure is formed within the support that both conducts heat and allows fluid to pass through the thermally conductive channel. c) inserting the flexible pipe into the center hole of the support body, ensuring that the flexible pipe is connected to the auxiliary flow channel; S3. Overall molding: a) Insert the inner frame into the elastic support net, and then coat the support layer after plasma treatment of the joint surface; b) After surface activation treatment, the phase change layer is hot-pressed with the support layer, and the pressure is controlled at 3-5 MPa to keep the phase change layer in a gel state; c) The wear-resistant surface is covered by a three-layer co-extrusion process, and small-diameter pipes are embedded in the grooves; d) Install the reservoir system and test the temperature control response threshold of the shape memory alloy spring.

[0057] The embodiments of the present invention are presented for purposes of illustration and description and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those skilled in the art. The embodiments are chosen and described in order to better illustrate the principles of the invention and its practical application and to enable those skilled in the art to understand the invention and design various embodiments with various modifications as suited for specific applications.

Claims

1. An anti-aging and wear-resistant cable, comprising a cable core and a cortex coated outside the cable core, characterized in that: The cortex includes a wear-resistant surface layer, a phase-change layer, and a support layer from outside to inside, and the cable core is covered by the support layer; the phase-change layer includes sealed cavities surrounded by elastic partitions, and adjacent cavities are connected through controllable valve channels. The cavities are filled with a thixotropic phase-changing body, which is in a gel state at rest and changes to a sol state under pressure. An elastic support net is provided in the support layer, and the elastic support net wraps the cable core.

2. The anti-aging and wear-resistant cable according to claim 1, characterized in that: The wear-resistant surface layer is composed of the following components in parts by mass: 100 parts of polyurethane matrix, 20-30 parts of silicon carbide micropowder (particle size 5-15 μm), 1-3 parts of graphene nanosheets (thickness ≤ 5 nm), and 0.5-1 part of antioxidant 1010.

3. The anti-aging and wear-resistant cable according to claim 2, characterized in that: The preparation process of the wear-resistant surface layer includes: S1. Mix the polyurethane matrix and silicon carbide micropowder in an internal mixer at a temperature of 120-140 °C for 15 minutes. S2. Add graphene nanosheets and antioxidant, and granulate by twin-screw extrusion. S3. Use a three-layer coextrusion die to coat the outside of the phase-change layer. The outer layer is a wear-resistant composite material, the middle layer is an EVA buffer layer with a thickness ratio of 20%, and the inner layer is conductive carbon black-modified TPU.

4. An anti-aging and wear-resistant cable according to claim 1, characterized in that: The thixotropic phase-changing body is composed of the following components: 70-80 wt% of white oil, 8-12 wt% of organic bentonite, 10-15 wt% of microencapsulated paraffin, and 1-2 wt% of nano-silica.

5. An anti-aging and wear-resistant cable according to claim 4, characterized in that: The preparation process of the thixotropic phase-changing body is: heat the white oil to 60 °C, then add organic bentonite and disperse it ultrasonically for 30 minutes; cool down to 40 °C, then add microencapsulated paraffin and nano-silica, and process it with a high-shear emulsifier at a rotation speed of 8000 rpm for 10 minutes.

6. The anti-aging and wear-resistant cable according to claim 1, wherein: The elastic partition is a polyurethane-carbon nanotube composite material, and piezoelectric ceramic fibers are dispersed therein. The surface of the elastic partition has corrugated protrusions.

7. An anti-aging and wear-resistant cable according to claim 1, characterized in that: The controllable valve channel includes: a channel body and a valve structure. The channel body is a conical hole, and the valve structure is a thin film covering the small end of the conical hole. A cross-shaped micro-slit is formed by laser processing in the center of the thin film.

8. An anti-aging and wear-resistant cable according to claim 1, characterized in that: An inner skeleton is also provided inside the support layer. The inner skeleton includes a flexible pipe in the center and a support body circumferentially arranged outside the flexible pipe. Adjacent support bodies form a fan-shaped area. The cable core includes multiple strands, and each strand is distributed in one of the fan-shaped areas. A heat-conducting channel communicating with the flexible pipe is provided inside the support body, and the flexible pipe is used to guide fluid for heat dissipation.

9. The anti-aging and wear-resistant cable according to claim 8, wherein: Small holes are formed in the wear-resistant surface layer. Small-diameter pipelines are arranged in the small holes. The small-diameter pipelines penetrate inward through the phase change layer and communicate with the heat conduction channels. The surface of the wear-resistant layer is concave to form an axially extending groove. The small holes are distributed on the bottom wall of the groove. A sealing strip is arranged at the opening of the groove. One end of the flexible pipeline is provided with an elastic membrane to form a blind end. One end of the cable is sleeved with a liquid storage bag. The liquid storage bag communicates with the groove. And the flexible pipeline communicates with the liquid storage bag through a return pipe. A radially extending shape memory alloy spring is arranged in the liquid storage bag. The expansion and contraction of the shape memory alloy spring can drive the liquid storage bag to expand or contract, so that the internal cold liquid is supplemented into the flexible pipeline through the return pipe.

10. A preparation process for an anti-aging and wear-resistant cable, the cable produced by the process having the structural features described in any one of claims 1-9, characterized in that, It includes the following steps: S1. Preparation of the phase change layer: a) Adopt an ultraviolet-cured polyurethane composite material, and form an axially extending hexagonal prism honeycomb structure through DLP printing. A 0.5-mm connecting part is reserved between adjacent honeycomb units; b) Use a picosecond laser to process a conical through-hole at the center of the connecting part, with a cone angle of 60°±5°; c) After the PVDF film is pre-coated with glue, cover the small end of the conical hole through vacuum hot pressing bonding; d) Use an excimer laser to process a cross-shaped micro-slit in the center of the film, with a slit width of 20-30 μm; e) Heat the thixotropic phase variant to the flowing state, and cool and solidify it after vacuum perfusion through the liquid injection port; S2. Preparation of the inner skeleton: a) Extrude and form a flexible pipeline; b) Set an auxiliary structure for preparing a heat conduction channel in the support mold. Pour liquid silicone into the support. Inject the liquid silicone into the mold. Embed a heat conduction graphite sheet before curing to form a heat conduction network. After the silicone is cured, a composite structure that conducts heat and allows fluid to pass through the heat conduction channel is formed inside the support; c) Insert the flexible pipeline into the central hole of the support to ensure that the flexible pipeline communicates with the auxiliary flow channel; S3. Integral molding: a) Put the inner skeleton into the elastic support net, and coat the support layer after plasma treatment of the joint surface; b) After the surface of the phase change layer is activated, thermally press and compound it with the support layer, and control the pressure at 3-5 MPa to keep the phase variant in the gel state; c) Adopt a three-layer co-extrusion process to coat the wear-resistant surface layer, and synchronously embed small-diameter pipelines at the groove position; d) Install the liquid storage bag system and test the temperature control response threshold of the shape memory alloy spring.

Citation Information

Cited By

  • Multi-core heat dissipation flexible cable

    CN121460290A